INTERRATER AND INTRARATER RELIABILITY OF MOVEMENT COMPETENCY - Pagaduan, Jeffrey; Kritz, Matthew (Silliman Journal, 2022)
This study establishes the interrater and intrarater reliability of Movement Competency Screen (MCS). Nine male and six female MCS video data from the national dragonboat team were utilized in the study. Prior to the video recording, the athletes performed a standardized warm-up followed by a 2-minute active rest. Two raters scored data for two occasions after 6 and 7 days respectively. Intraclass correlation coefficient (ICC), 95% confidence interval (95% CI), typical error (TE), typical error as a %CV, and smallest worthwhile change (SWC) were used to identify absolute and relative interrater and intrarater reliability. For Day 1, interrater relative reliability was 0.43 (ICC) with 95% CI (-0.08, 0.76). TE was 0.77 with 1.80 %CV and 0.63 SWC. In Day 2, interrater relative reliability was 0.56 ICC with 95% CI (0.09, 0.83). TE = 0.69, %CV was 1.50 and SWC was 0.53. Intrarater ICC for rater 1 was 0.98 with 95% CI ranging from 0.93 to 0.99. TE was 0.17, %CV was 0.05 and SWC was 0.18. Rater 2 posted .76 ICC with 95% CI range from 0.42 to 0.91. Also, TE was 0.52, %CV was 0.60 and SWC was 0.23. Interrater absolute reliability was marginal for both days. Interrater relative reliability was considered poor for Day 1 and moderate in Day 2. Absolute intrarater reliability was good for rater 1 and marginal for rater 2. Intrarater relative reliability was high for both raters.